Composição centesimal e colesterol da carne de jacaré-do-pantanal (Caiman yacare Daudin 1802) oriundo de zoocriadouro e habitat natural - Vicente Neto, João (2006)
They were used 12 animals, 06 (with average weight of 5.93 kg) originating from captivity, authorized by Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis (IBAMA), Mato Grosso state, Brazil, and 06 (with average weight of 6.78 kg) originating from natural habitat, every animals coming from municipal district of Cáceres, Mato Grosso state, Brazil. The samples were collected of the muscles ílio–ischio–caudalis and occipito–cervicalis medialis, tail and back, respectively. In those muscles they were determined: moisture, ethereal extract, protein and ashes. The lipids extraction was driven with chloroform/methanol (2:1). The cholesterol was determined by colorimeter in spectrophotometer. The cut tail of the alligators originating from captivity presented averages of 74.50; 24.20; 0.83; 0.91% and the cut back 76.20; 23.68; 0.49 and 0.99% for moisture, protein, ethereal extract and ashes, respectively. In the animals originating from natural habitat, the averages were 72.29; 21.83; 5.43 and 1.09% in the tail and 76.70; 21.93; 0.54 and 1.25% in the back (moisture, protein, ethereal extract and ashes, respectively). The cholesterol averages in the animals originating from captivity were of 48.82 and of 53.73 mg/100 g–1 in the tail and back, respectively. In the animals originating from natural habitat the averages were of 37.05 mg/100 g–1 in the tail and 40.61 mg/100 g in the back. Thus, the alligators originating from captivity presented thinner meat, than the alligators originating from natural habitat. When comparing the cuts, the tail presented higher protein and ethereal extract, while the neck presented higher moisture, ashes and cholesterol.